A practical and intelligent technique for coupling multiple neighboring microgrids at the synchronization stage. (September 2017) - Shahnia, Farhad; Bourbour, Soheil
Abstract: It is expected from a microgrid to supply its local demand independently; however, the load and generation intermittency may lead to overloading of a microgrid temporarily. It is suggested in the literature that this problem can be mitigated by importing the required power from one/more neighboring microgrid(s), after their temporary coupling. This paper focuses on the transition stage of forming a system of coupled microgrids. A suitable and practically applicable strategy is developed in this paper, which facilitates the appropriate connection of the microgrids. The performance of the developed strategy is evaluated by time-domain simulation studies in PSCAD/EMTDC.